SENSITIVITY PATTERNS OF PSEUDOMONAS AERUGINOSA ISOLATES OBTAINED FROM CLINICAL SPECIMENS IN PESHAWAR - Abbas, Syed Hussain; Khan, Muhammad Zia ul Islam; Naeem, Mohammad; Adil, Muhammad; Naz, Syeda Maria; Khan, Ayasha; Khan, Muhammad Usman (Journal of Ayub Medical College Abbottabad, 2015)
Background: Pseudomonas aeruginosa (P. aeruginosa) is a highly virulent opportunistic pathogen and a leading cause of nosocomial infections.Affected patients are often hospitalized in an intensive care unit, and are immuno-compromised as a result of disease and treatment. Suspected P. aeruginosa require timely, adequate and empirical antibiotic therapy to ensure improved outcomes. The purpose of the study was to find the sensitivity and resistance pattern of P. aeruginosa to various groups of drugs, in clinical isolates collected from two major tertiary care hospitals of Peshawar. Methods: Different clinical isolate were taken from patients admitted in various wards of Khyber Teaching Hospital and Lady Reading Hospital Peshawar. Results: A total of 258 clinical isolates were positive for P. aeruginosa out of 2058 clinical isolates. Pseudomonas showed high degree of resistance to third generation Cephalosporins (Ceftazidime, and Ceftriaxone) and moderate degree of resistance to Quinolones and Aminoglycosides (Ofloxacin, Ciprofloxacin, Levofloxacin and Amikacin). Low resistance was observed to different combinations (Cefoperazone+Sulbactum, Piperacillin+Tazobactum). Meropenem and Imipenem had negligible resistance. Conclusion: There is growing resistance to different classes of antibiotics. Combination drugs are useful approach for empirical treatment in suspected Pseudomonas infection. Imipenem and Meropenem are extremely effective but should be in reserve. Keywords: Pseudomonas aeruginosa, Drug sensitivity, Resistance pattern